2016
DOI: 10.1542/peds.2015-2542
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure, FASD, and Child Behavior: A Meta-analysis

Abstract: CONTEXT: Fetal alcohol spectrum disorders (FASD) and prenatal alcohol exposure (PAE) are associated with behavioral difficulties, although there are no published systematic reviews that summarize and critique the literature. OBJECTIVE:To describe the behavioral characteristics of children with PAE and/or FASD, assessed using the Achenbach System of Empirically Based Assessments (ASEBA) for schoolaged children with parent, teacher, and youth (self-report) forms.DATA SOURCES: Electronic literature databases, ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 36 publications
1
49
0
2
Order By: Relevance
“…Although the sample was demographically diverse, most children had clinically significant behavior problems and those with intellectual disabilities were purposefully excluded. Therefore, the data range may have been restricted in some ways and generalizability of findings possibly reduced (although behavioral difficulties are common in the FASD population 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the sample was demographically diverse, most children had clinically significant behavior problems and those with intellectual disabilities were purposefully excluded. Therefore, the data range may have been restricted in some ways and generalizability of findings possibly reduced (although behavioral difficulties are common in the FASD population 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association between prenatal substance exposure and childhood internalizing behaviors has received relatively less attention, though research has shown drug exposure to be associated with increased internalizing behaviors (Robinson et al, 2008; Tsang et al, 2016). Furthermore, prenatal substance exposure has been shown to affect the development of problem behavior in children as young as 3 and 5 years old, as well as the trajectory of adjustment difficulties across early childhood (Bada et al, 2007; LaGasse et al, 2012; Lester et al, 2009).…”
Section: Effects Of Prenatal Substance Exposure On Childhood Emotionamentioning
confidence: 99%
“…Physical effects include reduced birth weight, facial dysmorphology (long, flat philtrum, low nasal bridges, short palpebral fissures, thin upper lips, ear malformations, flattened maxilla, and epicanthal folds), as well as muscular, cardiac, and skeletal malformations (Feldman et al, 2012; Hofer and Burd, 2009). Prenatal alcohol exposure can also lead to neuropathology in a variety of brain regions (Donald et al, 2015; Riley et al, 2011) that affect an array of behavioral and cognitive domains, leading to learning impairments, attention deficits, motor dysfunction, altered social behavior, mood disorders, and changes in sleep and stress responses (Kelly et al, 2000; Mattson et al, 2011; Moore et al, 2014; Riley et al, 2011; Tsang et al, 2016). …”
Section: Introductionmentioning
confidence: 99%